Functional Somatic Symptoms in Children and Adolescents A Stress-System Approach to Assessment and Treatment - Kozlowska, Kasia; Scher, Stephen; Helgeland, Helene (Palgrave Texts in Counselling and Psychotherapy,, 2020)
"This book, at the intersection of mind-body medicine, is a must-read ... The authors have done a masterful job of linking together emerging cutting-edge biology with case-based discussions and practical treatment suggestions to aid the development of a mind-body program. Functional disorders are common in pediatrics, and this book is a major advance in bringing this set of conditions out of the shadows and into mainstream educational and clinical initiatives." - David L. Perez, MD, MMSc; Massachusetts General Hospital, Harvard Medical School, USA "A uniquely creative, well-informed, and authoritative account that uses the latest scientific and clinical research to inform clinical assessment and treatment of functional symptoms and syndromes in children and young people. The authors' stress-system model for understanding these experiences is complemented by the extensive use of clinical vignettes that are integrated into an overarching clinical framework that will prove useful for trainees and the broad range of clinicians addressing these problems in their own practices." - Elena Garralda, MD, MPhil, FRCPsych, FRCPCH, Emeritus Professor of Child and Adolescent Psychiatry, Imperial College London, UK This open access book sets out the stress-system model for functional somatic symptoms in children and adolescents. The book begins by exploring the initial encounter between the paediatrician, child, and family, moves through the assessment process, including the formulation and the treatment contract, and then describes the various forms of treatment that are designed to settle the child's dysregulated stress system. This approach both provides a new understanding of how such symptoms emerge - typically, through a history of recurrent or chronic stress, either physical or psychological - and points the way to effective assessment, management, and treatment that put the child (and family) back on the road to health and well-being. Kasia Kozlowska is a child and adolescent psychiatrist at The Children's Hospital at Westmead and Clinical Associate Professor of Psychiatry and of Child and Adolescent Health at the University of Sydney Medical School, Australia. Stephen Scher is Senior Editor, Harvard Review of Psychiatry, and Lecturer in Psychiatry, McLean Hospital, Harvard Medical School, USA, and the University of Sydney Medical School, Australia. Helene Helgeland is a child and adolescent psychiatrist at Oslo University Hospital. She is the head of Norway's National Advisory Unit on Complex Psychosomatic Disorders in Children and Adolescents.